Prognosis of Functional Results of Arising or Immature Cataract Phacoemulsification High Myopia - A. A. Pilyagina; O. A. Fabrikantov; S. V. Shutova (Oftalʹmologiâ)
Actuality. Complicated cataract surgery in high myopia is accompanied by the high risk of intra- and postoperative complications caused by this background disease. The presence of lens opalescence influences the results of many functional diagnostic tests. Diagnostic and prognostic research of the modern methods of investigation such as spectral optical coherence tomography, ultrasound biomicroscopy and B-scanning is urgent in patients with high myopia and cataract. The true prognosis of visual functions in these patients will allow solving the problem of cataract phacoemulsification expediency, decreasing the risks of complications.Purpose. To determine prognostic criteria of complicated cataract phacoemulsification outcome in high myopia.Patients and methods. 62 patients (101 eyes) with arising or immature cataract and high myopia were examined. All patients underwent ultrasound biomicroscopy of retinal periphery, ultrasound B-scanning of vitreous body and spectral optical coherence tomography of macular zone preoperatively, in the first postoperative days, in a month, in 6–8 months. We performed the correlation analysis of the initial morphological parameters and postoperative visual acuity. To solve the problem of the favorable outcome prognostication (achieving a certain level of visual acuity by the definite term after surgery) the method of binary logistic regression was used.Results and conclusion. The performed mathematical analysis showed the correlation between the postoperative visual acuity and the initial morphological parameters in a myopic eye: the value of ocular anterior posterior axis, the height of the posterior vitreous detachment, posterior staphyloma, the retinoschisis length in the superior outer segment, epiretinal membrane height, pigmented epithelium destruction and discharge, increased choroidal reflectivity, subfoveal choroidal thickness. We built the mathematical models that allowed predicting with high accuracy the probability of achieving a certain level of postoperative visual acuity following cataract phacoemulsification in high myopia.